Excellence in Women Basketball: Sport Career Development of World Champions and Olympic Medalists Brazilian Athletes - Galatti, Larissa Rafaela (2019)
This study investigated the career of seven Brazilian athletes who hold the title of world champions and Olympic medalists in basketball. The aim was to identify individual´s multiple factors that influenced them to reach the excellence level throughout their sport career. The data was collected through semi-structured retrospective interviews and was analyzed using Thematic Analysis, having the Personal Assets Framework as the main supporting theory. The results suggest that autonomous and diversified practice was essential for players’ development on the early years of their sport careers, as well as financial support on the specializing years. During the investment and maintenance years, intrapersonal skills have become more important, training time has increased and there was a disregard with social living; historically significant achievements and financial recognition provided a sense of reward and worth.